Effects of yeast extract supplemented in diet on growth performance, digestibility, intestinal histology, and the antioxidant capacity of the juvenile turbot (Scophthalmus maximus) - Sun, Jingwu; Li, Yahui; Ren, Tiancong; Gao, Qian; Yin, Lingqi; Liang, Yunzhi; Liu, Haiyan (Frontiers in Physiology, 2024)
An 8-week feeding experiment was conducted on juvenile turbot (Scophthalmus maximus) to evaluate the influence of yeast extract (YE) supplementation in diet on growth performance, feed utilization, body composition, nutrient digestibility, intestinal histology, antioxidant capacity. Four experimental diets were formulated with graded levels of yeast extract 0 (YE0), 1% (YE1), 3% (YE3), 5% (YE5), and fed to turbots (initial body weight: 4.2 ± 0.1g) with three replicates per diet and 200 fish in each replicate, respectively. The results showed that turbots fed with diets YE1 and YE3 displayed significantly higher specific growth rate and protein efficiency rate in comparison to those fed with diets YE0 and YE5, while the feed conversion ratios in YE1 and YE3 groups were lower than that of YE0 and YE5. Fish fed with diets YE3 and YE5 showed higher body crude protein contents than those in groups YE0 and YE1. The highest apparent digestibility coefficients for dry matter and crude protein, digestive enzyme activities (trypsin, lipase, and amylase), height of intestinal fold were observed in YE3 group. YE3 treatment displayed a significant higher superoxide dismutase (SOD) activity than YE0 group, while the malondialdehyde (MDA) content in YE1 was significantly lower than those in YE0 and YE5. No significant difference was observed in serum physiological and biochemical parameters among all treatments. Overall, appropriate dietary supplementation of yeast extract could improve the growth performance, digestibility and antioxidant capacity of juvenile turbot, and the recommended yeast extract level in feed is 2.47%.